Monocyte plasticity and HLA-DR expression in patients with X-linked agammaglobulinemia - Hasibe Artac; Ayca Ceylan; Ilknur Kulhas Celik; Figen Celebi Celik; Yasin Karali; Zeynep Meric; Demet Tekcan; Mehmet Geyik; Selcen Bozkurt; Saliha Esenboga; Zehra Şule Haskoloğlu; Esra Ozek Yucel; et al. (Immunologic Research, 2025)

Nonstationarity impacts on the assessment of drought conditions across diverse climate zones of Pakistan - Maryam; Rizwan Aziz; Ismail Yucel; Mahnoosh Moghaddasi; Muhammad Awais (Theoretical and Applied Climatology, 2025)

Nonstationarity assessment in extreme temperatures and its association with antecedent soil moisture levels across diverse climate zones in Pakistan - Darakshan Naeem; Rizwan Aziz; Mahnoosh Moghaddasi; Ismail Yucel; Muhammad Awais (Theoretical and Applied Climatology, 2025)

Investigating the comparative utility of ECMWF precipitation forecasts as an alternative to reanalysis data - Muhammad Amjad; M. Tugrul Yilmaz; Ismail Yucel; Koray K. Yilmaz; Kurtuluş Öztürk (Hydrological Sciences Journal, 2024)

Evaluation of the fully coupled WRF and WRF-Hydro modelling system initiated with satellite-based soil moisture data - Eren Duzenli; Ismail Yucel; M. Tugrul Yilmaz (Hydrological Sciences Journal, 2024)

An explainable two-stage machine learning approach for precipitation forecast - Ali Ulvi Galip Senocak; M. Tugrul Yilmaz; Sinan Kalkan; Ismail Yucel; Muhammad Amjad (Journal of Hydrology, 2023)

Time-independent bias correction methods compared with gauge adjustment methods in improving radar-based precipitation estimates - Kaveh P. Yousefi; M. Tugrul Yilmaz; Kurtuluş Öztürk; Ismail Yucel; Koray K. Yilmaz (Hydrological Sciences Journal, 2023)

Assessment of changes in return levels of historical and projected high and low flows of upper Euphrates basin in Turkey using nonstationary models - Rizwan Aziz; Ismail Yucel (Environmental Monitoring and Assessment, 2023)

Modification of reinforced hollow fiber membranes with WO3 nanosheets for treatment of textile wastewater by membrane bioreactor - Ismail Koyuncu; Bahriye Eryildiz; Recep Kaya; Yucel Karakus; Fatemeh Zakeri; Alireza Khataee; Vahid Vatanpour (Journal of Environmental Management, 2023)

Spatiotemporal trends in daily and subdaily rainfall extremes and return levels in Turkey - Derya Albayrak; Omer Lutfi Sen; Ismail Yucel (International Journal of Climatology, 2022)
In this study, we present the long‐term daily and subdaily station data of annual extreme rainfall (1970–2015) and the trend analyses in rainfall regimes in Turkey. Trends in 5, 10, 15, and 30 min, 1, 2, 6, 12, and 24 hr of extreme rainfall in seven different rainfall regimes are estimated through nonparametric tests. The trends in return levels (2, 20, and 100 years) are defined by an appropriate three‐parameter generalized extreme value distribution and are evaluated in the climatological context of rainfall regimes. Overall, from 5‐min to 2‐hr durations, magnitudes of trends in extreme rainfall constantly increase in all rainfall regimes, which may be attributed to the intensified contribution of convective rainfall as a response to warming. Trend analysis of return levels reveals that, compared with 2‐year return levels, low‐probability high‐impact extreme rainfall events generally have the lowest estimated median trends until 30‐min to 2‐hr range. A shift in the magnitudes of trends occurs generally at 30‐min and 1‐hr durations; trends of rare intense events increase at the expense of less intense extreme rainfall. Thus, the intensification of 1–2‐hr extreme rainfall events can arise from both the increasing trends of more common events in shorter rainfall durations and from the increase in the trends of low‐probability high‐impact extreme rainfall events at this range. Moreover, explicitly in continental rainfall regimes, increases in the magnitudes of the trends in 30‐min to 2‐hr duration range are accompanied by various declines in 6–24‐hr duration range. Although coastal regimes generally have increasing trend values from 5‐min to 24‐hr durations, in northern and southern clusters, changes occur in the variability of extreme rainfall and the trend values of rarer (20‐ and 100‐year return periods) extreme rainfall exhibit increases in 6–12‐hr range.

Correction to: Primary antibody deficiencies in Turkey: molecular and clinical aspects - Sinem Firtina; Yuk Yin Ng; Ozden H. Ng; Ayca Kiykim; Esra Yucel Ozek; Manolya Kara; Elif Aydiner; Serdar Nepesov; Yildiz Camcioglu; Esra H. Sayar; Ezgi Yalcin Gungoren; Ismail Reisli; et al. (Immunologic Research, 2022)

Primary antibody deficiencies in Turkey: molecular and clinical aspects - Sinem Firtina; Yuk Yin Ng; Ozden H. Ng; Ayca Kiykim; Esra Yucel Ozek; Manolya Kara; Elif Aydiner; Serdar Nepesov; Yildiz Camcioglu; Esra H. Sayar; Ezgi Yalcin Gungoren; Ismail Reisli; et al. (Immunologic Research, 2022)

Assessing nonstationarity impacts for historical and projected extreme precipitation in Turkey - Rizwan Aziz; Ismail Yucel (Theoretical and Applied Climatology, 2021)

Climate change impacts on extreme precipitation of water supply area in Istanbul: use of ensemble climate modelling and geo-statistical downscaling - Fatih Kara; Ismail Yucel; Zuhal Akyurek (Hydrological Sciences Journal, 2016)

Assessment of a flash flood event using different precipitation datasets - Ismail Yucel (Natural Hazards, 2015)

Climate change effects on extreme flows of water supply area in Istanbul: utility of regional climate models and downscaling method - Fatih Kara; Ismail Yucel (Environmental Monitoring and Assessment, 2015)

Climate change impacts on snowmelt runoff for mountainous transboundary basins in eastern Turkey - Ismail Yucel; Abdülkadir Güventürk; Omer Lutfi Sen (International Journal of Climatology, 2015)
This study investigates whether snowmelt runoff for the selected 15 streamflow stations located in the Euphrates, Tigris, Aras, and Çoruh basins in eastern Anatolia, Turkey, has shown a consistent hydrologic response to global climatic changes over the past several decades. It also investigates the future runoff changes in these basins. The analysis utilizes streamflow and meteorological data from 1970 to 2010 available within the study area to identify spatial and temporal patterns of trends in the seasonality of streamflow, temperature, and precipitation. Results indicate significant temperature increases (average 1.3 °C across the stations) over the time period. They also indicate increases in annual precipitation (average 7.5% across the stations) but the increases are not significant, in general. The streamflow timings in the mountainous basins are found to have already shifted to earlier days in the year (9 days on average), and this is a clear indication of earlier spring melting of snowpack due to increasing temperatures in recent years. Eight among fifteen stream gauging stations in the basins show significant time shifts in snowmelt runoff according to statistical trend tests (based on 90% confidence level). A regional climate change simulation based on a high emissions scenario suggests 10–30% declines in the annual surface runoffs of Aras, Euphrates, and Tigris basins and a slight increase (about 4%) in the annual surface runoff of Coruh basin by the end of the present century. It further indicates that the timing of the peak flows will continue to shift earlier (by about 4 weeks over the century) in response to further warming, increasing the fraction of winter runoff while decreasing the fraction of spring runoff in the year in all these basins.

Evaluating the hydro-estimator satellite rainfall algorithm over a mountainous region - Ismail Yucel; Robert J. Kuligowski; David J. Gochis (International Journal of Remote Sensing, 2011)

Effects of implementing satellite observed aerosols into a mesoscale atmosphere model - Emine Bay; Ismail Yucel; Tom Kovacs; M. Patrick Mccormick (International Journal of Remote Sensing, 2011)